INFORMATION TECHNOLOGY AND PROCESS RESEARCH - Khalimova Mohigul Rustamovna (Galaxy International Interdisciplinary Research Journal, 2022)
The use of information and communication technologies (ICT) in the classroom is one of the successful modern pedagogical teaching methods. Presentation is the presentation of information to the target audience, using visual aids.